Effects of Homeopathic Phosphorus on Encephalitozoon cuniculi-Infected Macrophages In-Vitro - Nagai, Mirian Yaeko; Dalboni, Luciane Costa; Cardoso, Thayná Neves; Correia, Michelle Sanchez; Pinto, Sandra Augusta G.; Pinto, Andreia A. G.; Coelho, Cideli de Paula; Alvarez-Saraiva, Anuska; Peres, Giovani B.; Lallo, Maria Anete; Bonamin, Leoni Villano (Homeopathy, 2019)
Introduction Encephalitozoon cuniculi (E. cuniculi), a fungus that acts as an intracellular pathogen, causes a marked neurological syndrome in many host species and is a zoonotic concern. Although no well-established treatment for this syndrome is known, previous successful clinical experience using homeopathic phosphorus has been described in which symptom remission with no mortality occurred in 40/42 animals by means of unknown immunological mechanisms. The latter observation was the main motivation for this study.Objective To verify, in an in-vitro model, if macrophages infected with E. cuniculi can change in function after treatment with different potencies of phosphorus.Materials and Methods RAW 264.7 macrophages were infected with E. cuniculi in-vitro and treated with various homeopathic potencies of phosphorus. The vehicle was used as a control solution (0.06% succussed ethanol). After 1 and 24 hours, the following parameters were analyzed: parasite internalization (by the Calcofluor staining method), lysosome activity (by the acridine orange method), cytokine/chemokine production (by the MAGPIX system), and cell ultrastructure. Automatic image analysis was used when applicable, and the experiments were performed in triplicate.Results Treatment with vehicle alone increased interleukin (IL)-6, tumor necrosis factor alpha and monocyte chemotactic protein -1 production (p ≤ 0.05) and reduced the number of internalized parasites (p ≤ 0.001). A progressive and time-dependent increase in RANTES (regulated on activation, normal T-cell expressed and secreted) and lysosome activity (p ≤ 0.002) was observed only after treatment with the highest potency of phosphorus (Phos 200cH), together with decreased apoptosis rate, intense parasite digestion, and the presence of non-internalized spores.Conclusions Phos 200 cH has a modulatory action on the activity of infected macrophages, especially a specific increase in RANTES, a key element in the prognosis of E. cuniculi-infected and of immunosuppressed patients bearing infections.
Keywords: homeopathy; fungus; microsporidiosis; cytokines; chemokines